The Reconfiguration of the State under Economic Conditionality and the Creation of Hollow Democracies ? With Illustrations from Zambia - Lloyd, Peter (2004)
This paper will explore the linkages and contradictions between the promotion of democracy and the application of economic and political conditionality in Southern Africa, with particular reference to Zambia. Many electoral democracies have emerged in Africa in the last decade in conjunction with and partially as a consequence of the conditions applied to loans by bilateral and multilateral donors. It will be argued that the process of conditionality and the neoliberal policies applied actually inhibit the emergence of substantive democracy and present a threat to the consolidation and longevity of even minimal forms of liberal democracy. The conditions applied to aid represent an attempt to reconfigure the activities, capacity and capabilities of the state. Most significantly, they involve the imposition of a neoliberal economic model which is seen as technically necessary to tackle economic crisis and which due to the leverage offered donors by the indebtedness of recipient countries is uncontestable, yet require active state intervention to achieve (Polanyi’s insight that the creation of self regulating markets require regulatory state activity). A major area of state policy is thus placed beyond accountability to the electorate of the recipient country; this is also true of many aspects of political and social policy. The process of negotiation between the International Financial Institutions and representatives of countries (most often the President and a small group of politicians and advisors from the finance ministry) also promotes a concentration of power within the state as representatives must be able to adopt positions on the behalf of their country and enact agreed policies from the top down. Conditionality thus involves a reduction in the democratic accountability of the state in three ways: Firstly, as political authority shifts upwards to the international sphere, to the IFIs and donor community; secondly as power is centralised within the presidency and finance ministry; thirdly, the scope of democracy is limited as liberalisation and the strict separation of politics and economics are enforced, placing many elements of economic life beyond the reach of democratic institutions. Applying this framework to Zambia, it will be argued that consequently a very limited and hollow form of democracy where most of the important political and economic processes affecting people’s lives are unaccountable to them has been created, and that increasing disillusionment and political volatility are ensuing, possibly representing a threat to even this minimal democracy.
Political Science
Keywords: South Africa; democracy; economics; international studies; political doctrines; political science